In Search for Another Master: Gabriel Tarde and French Classical Sociology Tradition - Fitramadhana, Rizqyansyah (Departemen Sosiologi Universitas Gadjah Mada, 2025)
Classical sociology is a theoretical domain that is often labelled outdated. Nevertheless, in the Sociology curriculum, almost all departments teach classical theory to their students. In Indonesia, several classical scholars like Auguste Comte, Herbert Spencer, Karl Marx, Ferdinand Tonnies, Max Weber, and Emile Durkheim have been consistently taught by sociology departments all over the universities. However, despite the unwavering effort to preserve classical tradition, there have been no scientific articles that reveal one of the founding fathers of French Sociology, Gabriel Tarde. This article attempts to respond to these shortcomings by bringing the fruits of Gabriel Tarde's thoughts to the surface. This study uses critical hermeneutics to explain key concepts initiated by Gabriel Tarde in a series of scientific works and biographies. In general, the study found two things. First, there are two dominant concepts in Gabriel Tarde's thought: imitation and monad. The idea of imitation is used by Tarde to explain how society exists, while the understanding of monads empowers Tarde to elaborate on the phenomenon of social change. Second, with the example of migrant workers and the processes of agricultural innovation, this paper endorses the application of Tarde’s theory of imitation and monads to explain myriad social phenomena in Indonesia. However, the article provides three criticisms toward Tarde: his blindness to economic or financial capital, the heavy reliance on natural science analogy, and the tendency of elitism and colonialism.